Lược đồ logic đối xứng và ứng dụng. Phần I: Khái niệm về lược đồ logic đối xứng - Vân, Phan Chí (Journal of Computer Science and Cybernetics, 2016)
In this paper author exposes the concept of the logical symmetric scheme which is a good logic mean for a knowledge presentation in the artificial intelligence demain. In the paragraph I: author exposes two original logic principle, four characteristic relations and eight logical deductive rules. In the paragraph II: author defines the concept of the logical symmetric scheme and his cores. He also exposes on the diagram and the graph of the logical symmetric scheme